Drug Resistance and Molecular Characteristics of Mycobacterium tuberculosis: A Single Center Experience - Li, Shanshan; Chen, Wen; Feng, Mengru; Liu, Yuejiao; Wang, Fenghua (Journal of personalized medicine, 2022)
In recent years, the incidence of tuberculosis (TB) and mortality caused by the disease have been decreasing. However, the number of drug-resistant tuberculosis patients is increasing rapidly year by year. Here, a total of 380 Mycobacterium tuberculosis (MTB)-positive formalin-fixed and paraffin-embedded tissue (FFPE) specimens diagnosed in the Department of Pathology of the Eighth Medical Center, Chinese PLA General Hospital were collected. Among 380 cases of MTB, 85 (22.37%) were susceptible to four anti-TB drugs and the remaining 295 (77.63%) were resistant to one or more drugs. The rate of MDR-TB was higher in previously treated cases (52.53%) than in new cases [(36.65%), p < 0.05]. Of previously treated cases, the rate of drug resistance was higher in females than in males (p < 0.05). Among specimens obtained from males, the rate of drug resistance was higher in new cases than in previously treated cases (p < 0.05). Of mutation in drug resistance-related genes, the majority (53/380, 13.95%) of rpoB gene carried the D516V mutation, and 13.42% (51/380) featured mutations in both the katG and inhA genes. Among the total specimens, 18.68% (71/380) carried the 88 M mutation in the rpsL gene, and the embB gene focused on the 306 M2 mutation with a mutation rate of 19.74%. Among the resistant INH, the mutation rate of −15 M was higher in resistance to more than one drug than in monodrug-resistant (p < 0.05). In conclusion, the drug resistance of MTB is still very severe and the timely detection of drug resistance is conducive to the precise treatment of TB.